2005
DOI: 10.1038/oby.2005.37
|View full text |Cite
|
Sign up to set email alerts
|

Best Practice Guidelines in Pediatric/Adolescent Weight Loss Surgery

Abstract: MICHAEL TARNOFF. Best practice guidelines in pediatric/adolescent weight loss surgery. Obes Res. 2005; 13:274 -282. Objective: To establish evidence-based guidelines for best practices in pediatric/adolescent weight loss surgery (WLS). Research Methods and Procedures:We carried out a systematic search of English-language literature in MEDLINE on WLS performed on children and adolescents. Key words were used to narrow the field for a selective review of abstracts. Data were extracted, and evidence categories w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0
5

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(75 citation statements)
references
References 56 publications
1
67
0
5
Order By: Relevance
“…This is particularly important for adolescents, because the long-term effects of bariatric surgery in younger, reproductively active populations have not been well characterized. 266,270,271 Given the limited quantity and scope of data on the risks and benefits of adolescent bariatric surgery, a conservative approach is needed.…”
Section: Case Seriesmentioning
confidence: 99%
“…This is particularly important for adolescents, because the long-term effects of bariatric surgery in younger, reproductively active populations have not been well characterized. 266,270,271 Given the limited quantity and scope of data on the risks and benefits of adolescent bariatric surgery, a conservative approach is needed.…”
Section: Case Seriesmentioning
confidence: 99%
“…6,7 On the basis of these factors, a number of pediatric groups have suggested that bariatric surgery is an appropriate treatment for carefully selected morbidly obese adolescents with severe comorbidities. [8][9][10][11] To date, a range of different types of bariatric procedures has been performed in this age group, including gastric bypass, vertical banded gastroplasty, and adjustable gastric banding.…”
Section: Arch Pediatr Adolesc Med 2007;161:217-221mentioning
confidence: 99%
“…In conclusion RYGB is to be recommended (Apovian et al 2005) as the procedure with the best long-term data and LAGB as the procedure with the least apparent risk for adolescent patients. Because there are currently no criteria to determine which of the two procedures (RYGB or LAGB) is best for any given patient, the decision should rest with the gender of the patient, the patient, the needed BMI-Loss, his or her parents or guardians, and the surgeon and other members of the team (pediatrician, psychologist, etc.)…”
Section: Restrictive Proceduresmentioning
confidence: 98%
“…comorbidities, and improved self-image and socialization (Apovian et al 2005;Inge et al 2004a;Dolan et al 2003;Stanford et al 2003;Capella and Capella 2003).…”
mentioning
confidence: 99%